2018
DOI: 10.1039/c8py00702k
|View full text |Cite
|
Sign up to set email alerts
|

A 1,2,3-triazolyl based conjugated microporous polymer for sensitive detection of p-nitroaniline and Au nanoparticle immobilization

Abstract: A 1,2,3-triazolyl based fluorescent CMP was used as an excellent chemosensor for p-nitroaniline detection and a support for Au catalyst deposition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 55 publications
0
32
1
Order By: Relevance
“…6), including ACN, DMF, acetone, THF, chloroform, DOX, and EtOH. 3,4,34 It was found that DP 4 A 0 and DP 4 A 2 disperse liquid in DMF, DOX, chloroform, and THF and exhibited purple or yellow emission when excited with 365 nm UV light. 6,35,36 Thanks to the completely p-conjugated skeleton from the connection of the phenyl rings, DP 4 A 0 and DP 4 A 2 exhibited the strongest uorescence in THF (l ex ¼ 370 nm) and DOX (l ex ¼ 365 nm) suspensions, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…6), including ACN, DMF, acetone, THF, chloroform, DOX, and EtOH. 3,4,34 It was found that DP 4 A 0 and DP 4 A 2 disperse liquid in DMF, DOX, chloroform, and THF and exhibited purple or yellow emission when excited with 365 nm UV light. 6,35,36 Thanks to the completely p-conjugated skeleton from the connection of the phenyl rings, DP 4 A 0 and DP 4 A 2 exhibited the strongest uorescence in THF (l ex ¼ 370 nm) and DOX (l ex ¼ 365 nm) suspensions, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…7c, good linear S-V relationships were observed for DP 4 A 0 and DP 4 A 2 , and the K sv were up to 4 orders of magnitude greater than before the addition of o-NP, which indicated that DP 4 A 0 and DP 4 A 2 have high sensitivity to o-NP. 5,23,34,38,39 In addition, the LODs of DP 4 A 0 and DP 4 A 2 to o-NP are 5.73 Â 10 À9 and 7.36 Â 10 À9 mol L À1 , respectively, also indicating a high sensitivity to o-NP. 4-6 Fig.…”
Section: Cmpsmentioning
confidence: 99%
See 2 more Smart Citations
“…The incorporation of heteroatom scaffolds as coordination groups was helpful to capture metal ions and guide the nucleation and growth of metal NPs. As a result, the interaction between support and loaded NPs was enhanced . The nitrogen‐rich triazine‐based porous polymers have attracted much attention in gas storage and separation, advanced semiconductors, fluorescent sensors, and energy storage .…”
Section: Methodsmentioning
confidence: 99%